Comparative analysis of immediate and delayed insertion of flexible cystoscope after application of topical anaesthetic lubricant on patient comfort - Bhat, Zubair; Wani, Mudassir (International Surgery Journal, 2019)
Background: The objective of the study was to compare the difference in pain scores during flexible cystoscopy between patients undergoing the procedure with insertion of the flexible cystoscope either immediately after topical lubrication with lignocaine gel or after a 3-minute delay. Methods: A total of 127 male patients with various indications for flexible cystoscopy were enrolled in this prospective study. Patients were randomized in two groups, immediate group and the delayed group depending on the retention time (immediate or after 3-minute delay) of the topical lignocaine gel. Pain scores were recorded immediately after the procedure using a visual analogue scale. The statistical analyses were performed using students “t” test. Results: Both the groups (immediate group and the delayed group) were comparable for variables including age, level of operating endoscopic surgeon and indication for the procedures. The most common indication for flexible cystoscopy was visible hematuria. There was no statistically significant difference in the mean pain scores between the two groups (p=0.98). However a small subset of patients (age less than 50 years), having flexible cystoscopy for the first time had less pain scores in the delayed group (p=0.003) but the sample size was very small. Conclusions: The study revealed that there appears to be no benefit in longer retention times of local anaesthetic during the outpatient flexible cystoscopy. However, there might be a possible advantage in men younger than 50 years of age who are having flexible cystoscopy for the first time.